Improved MANET Routing Protocols Performance using Optimization Methods - Ebady Manaa, Mehdi; Dheyaa Shamsi, Sadeem (International Journal of Engineering and Technology, 2018)
A Mobile Ad-hoc Network (MANET) is a combination of mobile nodes that contact and cooperate with one another without depending on any predefined infrastructure. Reactive protocols are on-demand routing protocols detect the routes between sender and receiver. These protocols do not keep any network topology information and there is no need to exchange routing information periodically so it saves much control overhead. Particle Swarm Optimization (PSO) algorithm is an inspired algorithm because it imitates the sociological behavior associated with bird crowd. PSO similar the other evolutionary algorithms based on population; PSO start with random solutions of the population. Bat algorithm (BAT) is a metaheuristic algorithm and its idea comes from the echolocation conduct of microbats, with disparity pulse averages of emission and loudness, used for global optimization. To address the problem of find in MANET optimal solution, BAT and PSO are used in this work by implementing 300000 scenario using AODV and DSR.After obtaining the resultsfrom these algorithms in comparison with DSR and AODV,It turns out that the use of optimization algorithms shows good results through increasing the packet delivery ratio and the reduction the delay and drop packets.Â